KURSUS SINGKAT DAN PELATIHAN PENGOLAHAN BUAH PISANG MENJADI PISANG SALE DAN TEPUNG PISANG DI DESA GUMRIH, KECAMATAN PEKUTATAN, KABUPATEN JEMBRANA - NOCIANITRI, KOMANG AYU; SUMIYATI, SUMIYATI; PUDJA, IDA AYU RINA PRATIWI; WIRAWAN, I PUTU SURYA; TIKA, WAYAN (Buletin Udayana Mengabdi; Vol 5 No 1 (2006): Volume 5 No.1 – April 2006, 2012)
ABSTRACT Banana is the main product of a dry land farming at Gumbrih. The shelf life of fresh banana is very short and hence it is a great effort to find out how to preserve the banana for longer period. A method that can be applied is that by processing the fresh banana into processed foods, which has longer shelf life and easily to be modified into several products, which still retains the flavour of fresh banana. It was found that the knowledge of the local people (Gumrih villagers) on technology and banana processing was quite low and hence the recent program on course and practices of banana processing into dried banana (pisang sale) and banana powder (tepung pisang) is absolutely important. The activities were held at Desa Gumbrih, Kecamatan Pekutanan, Kabuapten Negara, on Friday, 16 September 2005, attended by 26 participants. Instead of course and practical works, the activities also have been conducted by active two-direction discussion between participants and tutor members. Since participants were curious to follow all the activities and we suggest that similar program is significant to be held on those banana producers around Bali and the short practical course would be more beneficial if it can be associated with marketing of the products.